Pulmonary tuberculosis in infants under one year of age - Arıkan-Ayyıldız, Zeynep; Uzuner, Nevin; Çakmakçı, Handan; Uysal, Pınar; Fırıncı, Fatih; Tuncel, Tuba; Anal, Özden; Karaman, Özkan (The Turkish Journal of Pediatrics, 2011)
This study describes the clinical and radiological features of tuberculosis in infants under one year of age. Medical records were reviewed for infants aged 12 months or less with proven tuberculosis. Six patients’ data were evaluated. Cough and tachypnea were the major symptom and sign, respectively. Contact with an adult case of tuberculosis was present in five of the cases. Tuberculin skin test was positive in only one case. Mycobacterium tuberculosis was cultured from gastric aspirates of four of five infants and from cerebrospinal fluid in one case. Consolidation was the most common parenchymal lung lesion occurring in four of the patients. Mediastinal or hilar lymphadenopathies were also detected in four of the patients and calcifications were seen within the enlarged nodes in two of them. Antituberculous treatment appeared to be well tolerated without significant adverse effects. Significant radiological improvement was noted after a mean period of 4.6 months.